Serum autoantibodies against the dermal–epidermal junction in patients with chronic pruritic disorders, elderly individuals and blood donors prospectively recruited. (April 2014) - van, N.; Dohse, A.; Riechert, F.; Krull, V.; Recke, A.; Zillikens, D.; Schmidt, E.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Bullous pemphigoid (BP) is by far the most frequent autoimmune bullous dermatosis; it mainly affects the elderly, and is associated with severe pruritus. Autoantibodies against the epidermal basal membrane zone (BMZ) have previously been reported in patients with chronic pruritic dermatoses and elderly individuals. Therefore, chronic pruritus and old age were suggested as risk factors for BP. What does this study add? This prospective controlled study assayed sera from a large number of patients with pruritic dermatoses and elderly individuals using validated test systems and found no increased autoantibody reactivity against the epidermal BMZ compared with blood donors. Thus, old age and chronic pruritus do not appear to be factors for the development of autoantibodies against the epidermal BMZ.